2016
DOI: 10.1371/journal.pone.0165282
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of TaqMan Array Cards Data by an Assumption-Free Improvement of the maxRatio Algorithm Is More Accurate than the Cycle-Threshold Method

Abstract: Quantitative PCR diagnostic platforms are moving towards increased sample throughput, with instruments capable of carrying out thousands of reactions at once already in use. The need for a computational tool to reliably assist in the validation of the results is therefore compelling. In the present study, 328 residual clinical samples provided by the Public Health England at Addenbrooke's Hospital (Cambridge, UK) were processed by TaqMan Array Card assay, generating 15 744 reactions from 54 targets. The amplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…A custom TaqMan Array Card (TAC) spotted with lyophilized target-specific primers and probes was used to detect enteropathogens from the total NAE. The GASTRO v4.0K TAC was designed by MC at Public Health England (PHE), Cambridge, England [16] and manufactured by ThermoFisher, USA. GASTRO v4.0K screened for 28 enteropathogens: 12 viruses, 10 bacteria, 5 protozoa and 1 helminth (supplementary Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A custom TaqMan Array Card (TAC) spotted with lyophilized target-specific primers and probes was used to detect enteropathogens from the total NAE. The GASTRO v4.0K TAC was designed by MC at Public Health England (PHE), Cambridge, England [16] and manufactured by ThermoFisher, USA. GASTRO v4.0K screened for 28 enteropathogens: 12 viruses, 10 bacteria, 5 protozoa and 1 helminth (supplementary Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…A Rotarix ® vaccine-specific assay targeting the NSP2 gene was included to identify RVA vaccine shedding due to prior vaccination. The molecular probes were labeled at the 5’ end with 6-carboxyfluorescein (FAM) reporter dye and NFQ-MGB quencher dye at the 3’ end [16].…”
Section: Methodsmentioning
confidence: 99%
“…The FP method generated the Cq by registering the fractional cycle where the fluorescence passed the threshold of 0.2 units. The maxRatio transform of the amplification data and determination of the cut-offs were computed as previously described 9 , 10 . Different operators visually inspected the reaction’s profiles and classified each reaction as either passed or failed.…”
Section: Methodsmentioning
confidence: 99%
“…An alternative method, maxRatio, was introduced to overcome these issues 9 . It has been reported that maxRatio conferred a marginal increase in assay accuracy over FP 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…An alternative method, maxRatio, was introduced to overcome these issues 9 . It has been reported that maxRatio conferred a marginal increase in assay accuracy over FP 10,11 . FP provides only a quantification cycle (Cq) value, which is then used to calculate VL.…”
Section: Introductionmentioning
confidence: 99%